2007
DOI: 10.1039/b614678c
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the mechanism of methyl transfer during the biosynthesis of fosfomycin

Abstract: Hydroxyethylphosphonate is a required intermediate in fosfomycin biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
112
0
4

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 41 publications
3
112
0
4
Order By: Relevance
“…Discussion PEP mutase (PEPM) installs the P-C bond in all phosphonates for which the biosynthetic gene clusters are currently known. As part of a multidisciplinary program focused on naturally occurring phosphonates we have recently demonstrated that the gene clusters of these compounds can be readily identified using the pepM gene as a marker (3)(4)(5)(6)(7)(8)(9)(10). In addition, these studies have shown that phosphonate biosynthesis is widespread and that new clusters that encode for as yet structurally unidentified phosphonates are readily found (1).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Discussion PEP mutase (PEPM) installs the P-C bond in all phosphonates for which the biosynthetic gene clusters are currently known. As part of a multidisciplinary program focused on naturally occurring phosphonates we have recently demonstrated that the gene clusters of these compounds can be readily identified using the pepM gene as a marker (3)(4)(5)(6)(7)(8)(9)(10). In addition, these studies have shown that phosphonate biosynthesis is widespread and that new clusters that encode for as yet structurally unidentified phosphonates are readily found (1).…”
Section: Resultsmentioning
confidence: 95%
“…Other members mimic carboxyl groups or the tetrahedral intermediates formed during enzymatic metabolism of these moieties. Recent studies have started to reveal nature's biosynthetic strategies toward several of these compounds, including the clinically used antibiotic fosfomycin (2)(3)(4), the antimalaria clinical candidate FR900098 (5,6), the antifungal tripeptide rhizocticin (7), and the widely used herbicide phosphinothricin (8)(9)(10)(11)(12) (Fig. 1A).…”
mentioning
confidence: 99%
“…Previous studies in several laboratories have supported the fosfomycin biosynthetic pathway shown in Fig. 1 in Streptomyces fradiae and Streptomyces wedmorensis (37,50,59,60). Like in nearly all phosphonate biosynthetic pathways (39), the first committed step in fosfomycin biosynthesis in these streptomycetes is the conversion of phosphoenolpyruvate (PEP) to phosphonopyruvate (PnPy) (22,23,33).…”
mentioning
confidence: 99%
“…This thermodynamically unfavorable transformation is made feasible by linking it to the irreversible decarboxylation of PnPy to phosphonoacetaldehyde (PnAA) by a thiamine-dependent decarboxylase (41). Subsequent reduction to 2-hydroxyethylphosphonate (2-HEP) (51,59), methylation to generate 2-hydroxypropylphosphonate (2-HPP) (20,34,59,60), and epoxide formation (19,25,37,49,62) complete the biosynthesis of fosfomycin ( Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation